Multi-antigen avian influenza a (H7N9) virus-like particles: particulate characterizations and immunogenicity evaluation in murine and avian models. Issue 1 (December 2017) - Hu, Che-Ming; Chien, Chu-Yang; Liu, Ming-Tsan; Fang, Zih-Syun; Chang, Sui-Yuan; Juang, Rong-Huay; Chang, Shih-Chung; Chen, Hui-Wen
Abstract Background Human infection with avian influenza A virus (H7N9) was first reported in China in March 2013. Since then, hundreds of cases have been confirmed showing severe symptoms with a high mortality rate. The virus was transmitted from avian species to humans and has spread to many neighboring areas, raising serious concerns over its pandemic potential. Towards containing the disease, the goal of this study is to prepare a virus-like particle (VLP) that consists of hemagglutinin (HA), neuraminidase (NA) and matrix protein 1 (M1) derived from the human isolate A/Taiwan/S02076/2013(H7N9) for potential vaccine development. Results Full length HA, NA, and M1 protein genes were cloned and expressed using a baculoviral expression system, and the VLPs were generated by co-infecting insect cells with three respective recombinant baculoviruses. Nanoparticle tracking analysis and transmission electron microscopy were applied to verify the VLPs' structure and antigenicity, and the multiplicity of infection of the recombinant baculoviruses was adjusted to achieve the highest hemagglutination activity. In animal experiments, BALB/c mice and specific-pathogen-free chickens receiving the VLP immunization showed elevated hemagglutination inhibition serum titer and antibodies against NA and M1 proteins. In addition, examination of cellular immunity showed the VLP-immunized mice and chickens exhibited an increased splenic antigen-specific cytokines production. Conclusions The H7N9 VLPs possess desirable immunogenicity in vivo and may serve as a candidate for vaccine development against avian influenza A (H7N9) infection.